Understanding the Difference between Authentic Assessment and Traditional Assessment - Farida Nur Fatinah; Muamaroh; Mauly H.H; Yeny Prastiwi; Nur Hidayat (JPGENUS: Jurnal Pendidikan Generasi Nusantara, 2025)
This qualitative study aims to investigate the differences between traditional and authentic assessments in education in order to improve teaching and learning practices. Using a descriptive literature study method, this study analyses various relevant academic sources to identify the strengths and weaknesses of both types of assessments. The results show that authentic assessments are more effective in measuring critical thinking and problem-solving skills, while traditional assessments are more suitable for evaluating memorization and basic skills. The conclusion of the study recommends the use of a combination of both types of assessments to support deeper learning and better educational outcomes.